Resources and pace of leaving home among young adults in Poland. (9th August 2022) - Pustulka, Paula; Sarnowska, Justyna; Buler, Marta
ABSTRACT : Changes in the intergenerational family relationships are typically seen through the prism of contemporary parents supporting their children long into adulthood, offering their households as 'feathered nests' during extended transitions to adulthood. However, the majority of research in this realm comes from established welfare states of Western Europe and the Commonwealth and less explicitly addresses inequalities that mark these processes. Drawing on qualitative longitudinal research on transitions to adulthood in Poland, we use a data set of 127 interviews with university students and graduates to illustrate the process of leaving home in the Central and Easter European context. The paper accounts for both the objective (extensive/limited economic capital or resources) and subjective (fast/slow pace) dimensions crucial for how young people move out from parental homes. Our main contribution is a typology of Temporizers, Gymnasts, Runaways and Protectors as ideal types of pathways to leaving home in Poland.